AN AUDIT OF THE COMPLICATIONS OF DUAL AND SINGLE CHAMBER PACEMAKER IN ADULT PATIENTS FOLLOWED OVER A PERIOD OF ONE YEAR - Khan, Zahoor Ahmad; Sawar, Shah; Ullah, Kashif; Awan, Zahid Aslam (Journal of Postgraduate Medical Institute, 2012)
Objective: To determine the frequency of dual and single chamber pacemaker complications in adults. Methodology: This study was conducted in 151 pacemaker implanted patients and they were followedevery month for 1 year, for evaluation / programming of pacemaker function and examining for devicerelated complications. Results: Out of 151 patients with pacemaker, 111(73.5%) patients received single chamber pacemaker and40(26.5%) patients were implanted with dual chamber pacemakers. In one year follow up 21(13.9%)patients developed different complications while 130 patients had uneventful follow up. The differentcomplications seen were infection 9(6%) patients, lead displacement 4(2.6%) patients, heart failure3(2.0%) patients, Pacemaker syndrome, lead fracture, diaphragmatic twitching, pocket hematoma andkeloid formation at scar site was noted in 1(0.7%) patient each. As a whole complications in singlechamber was 73.5% compared to patient with dual chamber pacemaker which was 26.5%. Conclusion: The rate of complications associated with PPM is not significant, but the rate ofcomplications were more in single chamber pacemaker compared to dual chamber pacemaker. Infectionwas the major complication seen.